Activity of childhood lupus nephritis is linked to altered T cell and cytokine homeostasis - Edelbauer-Wechselberger, Monika; Billing, Heiko; Tönshoff, Burkhard (Journal of clinical immunology, 2012)
PurposeStandard therapy for lupus nephritis is based on non-specific immunosuppression. We aimed to identify specific alterations in T cell and cytokine homeostasis and possible associations with disease activity in children with lupus nephritis (LN).MethodsThe phenotype of circulating T cells from children with LN and healthy controls (HC) was analyzed by flow cytometry. Intracellular expression of IL-17 and INF-γ was assessed after stimulation with anti-CD3 and anti-CD28. Serum concentrations of IP10, CCL2, TGF-β, IL-17, and IL-23 were measured by ELISA. Disease activity was determined using the Systemic Lupus Erythematosus Disease Activity Index 2000 update (SLEDAI-2K).ResultsChildren with active LN displayed increased frequencies of effector memory CD4+CD45RO+CCR7− and terminal differentiated CD4+CD45RA+CCR7− T cells and reduced naive CD4+CD45RA+CCR7+ T cells compared to those with inactive LN or HC. Circulating CD4+CXCR3+ and CD4+CCR2+ T cells correlated inversely with the renal SLEDAI-2K, whereas IP10 and CCL2 showed a positive correlation. Reduced CD4+Foxp3+ T cells and serum TFG-β levels in active LN were associated with high serum IL-17 and IL-23 levels and correlated inversely with the renal SLEDAI-2K (r = −0.5855, p = 0.0013 and r = −0.6246, p = 0.0005, respectively), whereas IL-17 and IL-23 correlated positively (r = 0.5516, p = 0.0029 and r = 0.6116, p = 0.0007, respectively). Expansion of Th17 and Th1/Th17 cells in children with LN was significantly greater than in HC (p = 0.0304 and p = 0.0067, respectively).ConclusionChildren with active LN display high levels of pro-inflammatory cytokines associated with an increase in effector T cells and reduction of regulatory T cells. Therapeutic regulation of the aberrant cytokine profile might specifically interrupt pathogenic mechanisms.
Gesehen am 18.04.2019